2019
DOI: 10.1016/j.ejmp.2019.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Dose optimisation in paediatric radiography – Using regression models to investigate the relative impact of acquisition factors on image quality and radiation dose

Abstract: Objective: To investigate the optimum pelvis X-ray acquisition factors for a 10-year-old child. Secondly, to evaluate the impact of each acquisition factor on image quality (IQ) and radiation dose. Method: Images were acquired using a pelvis phantom and a range of acquisition parameters; e.g. tube potential, additional filtration and source-to-image distance (SID). Automatic exposure control (AEC) was used with two orientations (head towards/away from two outer chambers) and three different chamber selections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The role of additional filtration is essentially to reduce skin dose as it removes lower-energy photons from the X-ray beam, which are completely absorbed by the patient and do not contribute to the creation of the radiological image, while increasing the radiation dose [ 14 , 15 ]. This result is consistent with multiple previous studies that have shown a reduction in radiation dose using aluminum, copper, or compound additional filtration for thoracic [16] , [17] , [18] and abdominal X-rays [ 19 , 20 ] in adults, pelvic X-rays in children [22] , [23] , [24] , and thoracic [25] , [26] , [27] , [28] and pelvic [22] X-rays in newborns.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The role of additional filtration is essentially to reduce skin dose as it removes lower-energy photons from the X-ray beam, which are completely absorbed by the patient and do not contribute to the creation of the radiological image, while increasing the radiation dose [ 14 , 15 ]. This result is consistent with multiple previous studies that have shown a reduction in radiation dose using aluminum, copper, or compound additional filtration for thoracic [16] , [17] , [18] and abdominal X-rays [ 19 , 20 ] in adults, pelvic X-rays in children [22] , [23] , [24] , and thoracic [25] , [26] , [27] , [28] and pelvic [22] X-rays in newborns.…”
Section: Discussionsupporting
confidence: 93%
“…Copper and aluminum are commonly used materials for this purpose in medical imaging. Numerous studies have demonstrated the benefits of additional filtration for thoracic [16] , [17] , [18] , abdominal X-rays [ 19 , 20 ] and even thoracic CT [21] in adults, as well as for pelvic X-rays in children [22] , [23] , [24] . In newborns, it has been shown that additional filtration can reduce radiation dose without compromising the quality of thoracic [25] , [26] , [27] , [28] and pelvic X-rays [22] .…”
Section: Introductionmentioning
confidence: 99%
“…AEC is designed to keep image noise constant. It automatically adjusts the tube current to ensure that photons absorbed by the air between the object and the source are replenished in sufficient quantity to produce a high-quality diagnostic image (13). In the manual exposure system, the tube current is set based on the preselected current.…”
Section: Discussionmentioning
confidence: 99%
“…Children were used in studies on dose optimization and image quality by altering parameters, one of which was tube current-time. Radiation exposure is monitored with a dosimeter [25] and used to conduct an assessment of image quality together with the AEC variation [26].…”
Section: Introductionmentioning
confidence: 99%